The Role of Acceptance and Commitment (ACT) Therapy in Addressing Future-Oriented Anxiety in Adolescents and Young Adults: A Systematic Literature Review - Sandra, Agnes; Septika Natalia Anggraeni, Dara; Pratomo, Yuwono (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Future-related anxiety has become an increasingly prevalent psychological challenge among university students and adolescents, especially in the context of academic pressure, social demands, and global uncertainty. One promising intervention approach to address this issue is Acceptance and Commitment Therapy (ACT), which emphasizes psychological flexibility, acceptance of internal experiences, and commitment to personal values. This study aims to systematically review the effectiveness of ACT in managing future anxiety and its relation to psychological flexibility and future orientation. The research method employed is a Systematic Literature Review (SLR) based on the PRISMA framework, involving 20 selected articles obtained from various academic databases and filtered through rigorous inclusion criteria. Analysis was conducted through content evaluation, thematic synthesis, and visual bibliometric mapping using VOSviewer software. The findings indicate that ACT is effective in reducing anxiety, depression, stress, and trauma across various populations and delivery formats, including individual therapy, group interventions, online platforms, and in special populations. Furthermore, psychological flexibility and adaptive future orientation were consistently identified as key mediators contributing to improved psychological well-being. This study recommends the integration of ACT into higher education settings as a promotive and preventive mental health strategy for students facing future uncertainties. Kecemasan terhadap masa depan merupakan salah satu tantangan psikologis yang semakin banyak dialami oleh mahasiswa dan remaja di tengah tekanan akademik, sosial, dan ketidakpastian global. Salah satu pendekatan intervensi yang relevan untuk mengatasi persoalan ini adalah Acceptance and Commitment Therapy (ACT), yang menekankan pada fleksibilitas psikologis, penerimaan pengalaman internal, dan komitmen terhadap nilai-nilai hidup. Penelitian ini bertujuan untuk meninjau secara sistematis efektivitas ACT dalam mengelola kecemasan masa depan serta hubungannya dengan fleksibilitas psikologis dan orientasi masa depan. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan pendekatan PRISMA, mencakup 20 artikel yang diperoleh dari berbagai basis data ilmiah dan telah melewati proses seleksi berdasarkan kriteria inklusi yang ketat. Analisis dilakukan melalui penilaian isi artikel, sintesis tematik, dan pemetaan visual dengan bantuan perangkat lunak bibliometrik VOSviewer. Hasil tinjauan menunjukkan bahwa ACT terbukti efektif dalam mengurangi kecemasan, depresi, stres, dan trauma, baik dalam format individual, kelompok, daring, maupun pada populasi khusus. Fleksibilitas psikologis dan orientasi masa depan yang adaptif juga terbukti berperan sebagai mediator penting dalam meningkatkan kesejahteraan psikologis. Penelitian ini merekomendasikan penerapan ACT dalam konteks pendidikan tinggi sebagai strategi promotif dan preventif kesehatan mental mahasiswa.